Influence of menstrual cycle on indices of contraction-induced muscle damage - Markofski, M. M.; Braun, W. A. (The Journal of Strength and Conditioning Research, 2014)
Limited evidence suggests women exhibit a dampened response to contraction-induced muscle damage (CIMD). The purpose of this study was to examine if differences in symptoms of CIMD exist when induced in the menstrual cycle follicular or luteal phase. Sixteen resistance exercise trained women between the ages of 18-37 completed 75 eccentric-biased extension exercises with their nondominant arm. Creatine kinase (CK), elbow joint angles, arm volume, strength, and soreness were measured over 7 days. Estrogen was higher (p < 0.001) in the luteal group. The high estrogen group (luteal) had an overall greater strength decrement and higher CK concentration at 96 hours. Significant time effects were present for CK, elbow extension, elbow flexion, arm volume, and soreness. With the exception of strength and CK, signs and symptoms of CIMD were independent of menstrual cycle phase. Estrogen concentration in women may have limited effects on symptoms associated with muscle damage, but further research in this area is warranted.